Ida Scudder, healing bodies, touching hearts - Benge, Janet, 1958-; Benge, Geoff, 1954- (Hyderabad, India GS Books, 2017)
A biography of the twentieth-century American missionary doctor to India who pioneered rural health care and the training of Indian women as doctors and nurses, and who founded Vellore Christian Medical College and Hospital.
"The devil is coming!" -- "A better place to live" -- "I will make my own way in the world" -- "Together again" -- "There is something I can do about it" -- Dr. Ida Sophia Scudder -- Provision -- The Mary Taber Schell Memorial Hospital -- Roadside -- An animal-less carriage -- "So you are the woman?" -- The top medical school in the district -- A large garden to water -- A coeducational college -- Time to retire -- Her legacy remained alive.
Includes bibliographical references (p. 190).
Keywords: Scudder, Ida Sophia, -- 1870-1960. -- Juvenile literature; Scudder, Ida Sophia, -- 1870-1960.; Missionaries, Medical -- India -- Juvenile literature; Missionaries; Physicians; Women -- Biography